Overexpression, purification and assessment of cyclosporin binding of a family of cyclophilins and cyclophilin-like proteins of the human malarial parasite Plasmodium falciparum - BELL, ANGUS; MARIN MENENDEZ, ALEJANDRO (My University, 2011)
Malaria represents a global health, economic and social burden of enormous magnitude. Chemotherapy is at the moment a largely effective weapon against the disease, but the appearance of drug-resistant parasites is reducing the effectiveness of most drugs. Finding new drug-target candidates is one approach to the development of new drugs. The family of cyclophilins may represent a group of potential targets. They are involved in protein folding and regulation due to their peptidyl-prolyl cis-trans isomerase and/or chaperone activities. They also mediate the action of the immunosuppressive drug cyclosporin A, which additionally has strong antimalarial activity. In the genome database of the most lethal human malarial parasite Plasmodium falciparum, 11 genes apparently encoding cyclophilin or cyclophilin-like proteins were found, but most of these have not yet been characterized. Previously a pET vector conferring a C-terminal His6 tag was used for recombinant expression and purification of one member of the P. falciparum cyclophilin family in Escherichia coli. The approach here was to use an identical method to produce all of the other members of this family and thereby allow the most consistent functional comparisons. We were successful in generating all but three of the family, plus a single amino-acid mutant, in the same recombinant form as either full-length proteins or isolated cyclophilin-like domains. The recombinant proteins were assessed by thermal melt assay for correct folding and cyclosporin A binding.
PUBLISHED
Keywords: Immunology; malaria; Immunology, Inflammation & Infection; International Development